Determination of Fatty Acid Profile and Antioxidant Capacity of Rheum ribes L. Plant Growing in Ovacık District of Tunceli Province - Tolan, Ramazan; Güvenç, Mehmet; Okutan, Tuba (ABADER (Adiyaman Bilimsel Arastirmalar Dernegi), 2025)
In this study, the antioxidant capacity, total phenolic, flavonoid, protein, and fatty acid contents of Rheum ribes were evaluated. The plant material was collected from the Ovacık district of Tunceli Province, located in Eastern Anatolia, Türkiye. Methanol extracts were prepared and subjected to various spectrophotometric analyses. Antioxidant activity was assessed using DPPH (2,2-difenil-1-pikrilhidrazil) and ABTS (2,2'-azino-bis(3-etilbenzotiazolin-6-sülfonic acid) radical scavenging assays, total phenolic content was determined by the Folin–Ciocalteu method, flavonoid content by a colorimetric method, total protein content by the Bradford method, and fatty acid content by Gas chromatography (GC). According to the DPPH and ABTS assays, the extracts demonstrated strong radical scavenging activity, with inhibition percentages ranging between 93% and 99%. Total phenolic contents were calculated as 252.10, 267.28 and 267.97 mg GAE/g, while total flavonoid contents were found to be 7.89, 8.14, and 8.23 µg catechin equivalent/g. The average protein content was determined as 68.58 mg/g. The findings reveal that Rheum ribes possesses a high antioxidant potential and that it is rich in phenolic and flavonoid compounds. Additionally, its high protein content suggests that the plant may have structural and metabolic supportive properties beyond its antioxidant effects. These results indicate that it could be a promising candidate for use in the development of functional foods and pharmaceutical formulations. © 2025 ABADER (Adiyaman Bilimsel Arastirmalar Dernegi). All rights reserved.
Tunceli İli Ovacık İlçesinde Yetişen Rheum ribes L. (Işkın) Bitkisinin Yağ Asidi Profili ve Antioksidan Kapasitesinin Belirlenmesi
Keywords: DPPH free radical scavenging activity; fatty acids; flavonoid determination; protein content; Total phenolic content